Urban Terrorism: St. Peter’s Square, Vatican City - Daniel Tan (Footprint)
In the wake of the 2015 Paris attacks that claimed 130 lives, and in response to FBI warnings about threats by the Islamic State terrorist group, stringent security measures were pre-emptively imposed on St. Peter’s Square in Vatican City to deter possible attacks. The very nature of exclusion and control brought about by the securitisation corrodes the inherent nature of what the square previously symbolised: a sanctuary where all could enter and be welcome. Using the case of St. Peter’s Square, this work illuminates the three main contradictions between security and architecture apparent in practice today, as a way to understand the role of architecture in contributing to a convivial city under the conditions of terrorism.